One country, two crises: what Covid-19 reveals about health inequalities among BAME communities in the United Kingdom and the sustainability of its health system? - Akaninyene Otu; Bright Opoku Ahinkorah; Edward Kwabena Ameyaw; Abdul-Aziz Seidu; Sanni Yaya (BMC, 2020)
Abstract There has been mounting evidence of the disproportionate involvement of black, Asian and minority ethnic (BAME) communities by the Covid-19 pandemic. In the UK, this racial disparity was brought to the fore by the fact that the first 11 doctors to die in the UK from Covid-19 were of BAME background. The mortality rate from Covid-19 among people of black African descent in English hospitals has been shown to be 3.5 times higher when compared to rates among white British people. A Public Health England report revealed that Covid-19 was more likely to be diagnosed among black ethnic groups compared to white ethnic groups with the highest mortality occurring among BAME persons and persons living in the more deprived areas. People of BAME background account for 4.5% of the English population and make up 21% of the National Health Service (NHS) workforce. The UK poverty rate among BAME populations is twice as high as for white groups. Also, people of BAME backgrounds are more likely to be engaged in frontline roles. The disproportionate involvement of BAME communities by Covid-19 in the UK illuminates perennial inequalities within the society and reaffirms the strong association between ethnicity, race, socio-economic status and health outcomes. Potential reasons for the observed differences include the overrepresentation of BAME persons in frontline roles, unequal distribution of socio-economic resources, disproportionate risks to BAME staff within the NHS workspace and high ethnic predisposition to certain diseases which have been linked to poorer outcomes with Covid-19. The ethnoracialised differences in health outcomes from Covid-19 in the UK require urgent remedial measures. We provide intersectional approaches to tackle the complex racial disparities which though not entirely new in itself, have been often systematically ignored.